PENGARUH PROFITABILITAS, OPINI AUDITOR, DAN UKURAN PERUSAHAAN TERHADAP KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN di BURSA EFEK INDONESIA PERIODE TAHUN 2012-2014 - Hefi Dwi Oktavia; Diah Hari Suryaningrum (Jurnal Keuangan dan Bisnis, 2018)
Financial reporting is a source of information that can be used for business decision making. The faster the financial statements are conveyed, the information contained therein is more useful, and users of financial statements can make better decisions, both in terms of quality and time. But in reality some companies still get sanctions for delays in financial reporting. Therefore, this study aims to examine and prove empirically the factors that cause delays in reporting, namely profitability, auditors’ opinion, and company size. The population of this study is food and beverages companies listed on the Indonesia Stock Exchange for the period 2012-2014, with a sample of 12 companies with the observation period of 2012 to 2014. The sampling method used was purposive sampling. The analytical method used is Logistic Regression. The data used in this study are the financial statements and independent audit reports of each published company. The results of the study prove that the factors of profitability, auditors’ opinion, and company size do not affect the timeliness of the submission of financial statements. This implies that the company's awareness to submit financial statements is caused by other conditional conditions that were not examined in this study.